The Influence of Tourist Motivation on Revisit Intention to Alas Harum Agro tourism of Gianyar Regency, Bali - Sekali, Pebrianita Ivana Karo; Suryawardani, I Gusti Ayu Oka; Dewi, Ratna Komala (E-Journal of Tourism, 2020)
The positive perception of tourists about tourist attraction will give satisfaction to tourists which in turn will create intention to revisit. This study aims to analyze the influence of motivation (intrinsic and extrinsic) on the tourists’ satisfaction of Alas Harum Agrotourism, and analyze the effect of tourist satisfaction to revisit intention. The purpose of this study is also to evaluate the contribution of Alas Harum Agrotourism to the welfare of the community and surrounding farming families. The research data was processed in quantitative data using the Smart-PLS version 3.0 program and qualitative data was processed with descriptive analysis. The number of respondents in this study was 50 respondents. The results showed that intrinsic and extrinsic motivation had a significant effect on tourist satisfaction (P = 0,000). Tourist satisfaction has a significant effect on revisit intention (P = 0,000). The results also showed that Alas Harum Agrotourism contributed both to the community and surrounding farmers. Based on the results of the study, it is expected that Alas Harum Agro tourism can improve the quality of services and be able to maintain the beauty of nature to increase the motivation of tourists, that are having good results already. Keywords: tourist motivation, visitor satisfaction, revisit intention, partial least square